New insights in fluid monitoring for surgical patients. A concept study - Andrijauskas, Audrius; Andrijauskas, Povilas; Dilijonas, Darius; Jovaiša, Tomas; Marozas, Vaidotas; Stankevičius, Edgaras; Kerroum, Axel; Čincikas, Darius; Švedienė, Saulė; Kvederas, Giedrius; Porvaneckas, Narūnas; Svensen, Christer (Frontiers in Medical Technology, 2025)
PurposeThis study evaluates the primary hypothesis of red cell mass (RCM) dependent amplitude of homeostatically acceptable limits of fluctuation in plasma dilution by exploring the correlation between RCM-specific equilibrated hematocrit (EQ_Hct) and amplitude of plasma dilution during perioperative mini Volume Loading Test (mVLT).Materials and methodsWe retrospectively analyzed data from our previous RCTs, including 1,651 invasive arterial plasma dilution (aPD), 1,645 noninvasive “capillary” plasma dilution (cPD) and 236 estimates of EQ_Hct from 236 perioperative mVLT sessions. The cPD was estimated using noninvasive hemoglobin (SpHb, Masimo Radical 7, Irvine, CA) measurement. Fixed number of crystalloid boluses was used in 36 and 48 elective total knee arthroplasty (TKA) patients, and individualized number of boluses in 34 total hip arthroplasty (THA) patients for whom the number of boluses depended on the advices by our prototype automated clinical decision support system (ACDSS).ResultsThe primary hypothesis was confirmed—aPD decreased as EQ_Hct decreased when EQ_Hct <40%, and a very weak positive correlation was found between EQ_Hct and absolute aPD (Spearman's correlation coefficient 0.1025, p < 0.001). It was also confirmed when non-invasive data sets were used. A very weak negative correlation between HctEQ values and absolute cPD values (Spearman's correlation coefficient 0.0640, p = 0.0149).ConclusionThis study points to the feasibility of Photoplethysmography (PPG) based estimates of hemoglobin concentration for continuous noninvasive monitoring of fluid accumulation and detecting imminent edema using the Homeostatic Blood States (HBS) theory and transcapillary reflux model. The ACDSS-guided fluid loading has a potential to minimise unnecessary fluid accumulation. Further research is needed to explore and improve these techniques.